Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Answer:
Since g(f(x))=x g ( f ( x ) ) = x , f−1(x)=x9+13 f - 1 ( x ) = x 9 + 1 3 is the inverse of f(x)=9x−3 f ( x ) = 9 x - 3
Answer:
y = x + 3/9
Step-by-step explanation:
- Change f(x) y = 9x-3
Solve for y +3 +3
x+3 = 9y = y=x+3/9
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.